Are twin currency and debt crises special? - Christian Bauer; Bernhard Herz; Volker Karb (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2006)
In the literature on currency and banking crises it has become the standard procedure to distinguish pure currency crises, pure banking crises and combined ('twin') currency and banking crises. We show theoretically and empirically that a similar differentiation should be chosen with regard to currency and debt crises. Twin currency and debt crises differ from both pure currency and pure debt crises in their determinants, course of events, and economic consequences. We find that each type of crises has a unique set of macroeconomic causes. We also identify internal contagion and selection bias effects, which may lead to biased empirical estimates if twin crises are not treated as a specific type of crises. Such a separation allows to significantly improve the efficiency of early warning systems especially for debt and twin crises.
Keywords: F31; F33; F34; F41; 330; currency crises; debt crises; twin crises; emerging markets